Akuntabilitas Finansial, Transparansi dan Partisipasi Masyarakat dalam Pengelolaan Dana Desa: Studi di Kampung Margorukun Distrik Oransbari - Anik Wuriasih (Pusat Penelitian Pemberdayaan Fiskal dan Ekonomi Daerah (P3FED) Universitas Papua, 2021)
Purpose of this study was to determine and analyze the effect of income, the number of dependents, and premium prices on the demand for BPJS health services at Wosi Health Center, West Manokwari District, Manokwari Regency. The analytical method used is the quantitative descriptive analysis method with interview guides and questionnaires as instruments. Data analysis was performed using multiple linear regression analysis. The results showed that simultaneously the income variable, the number of dependents, and the premium price, had a significant effect, while partially only the number of dependents had a significant effect on the demand for BPJS health services at the Wosi Health Center